(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
The present work is based on a research work whose objective is to "Evaluate the feasibility of developing an e-blended proposal for the UTN Industrial Engineering career, based on an analysis of the curriculum design at a general level and of the elective subjects in particular". Within the framework of the thematic area: Education and taking into account the strategic area of application to the Ord. 1627 that creates the SIED (EaD System) in the UTN, the analysis of the research problem is justified by considering the lack of its implementation in undergraduate careers, especially in engineering, for this reason an a priori analysis is proposed in the Industrial Engineering career. To do this, the curriculum will be revised, not from the usual outline, but from a completely different and innovative approach, oriented to the development of competences. Methodological development will be carried out using techniques based on complementarity (analysis from different perspectives, including qualitative and quantitative strategies and data), such as methodological triangulation (use and contrast of multiple methods, data varieties, researchers and theories, in the study of the same object) following the methodological proposal of Sampieri (2006) and Castillo Arredondo and Medina Rivilla (2003). The standards of accreditation of engineering careers established by CONFEDI raise the paradigmatic disequilibrium in the training and evaluation of engineering students. This change affects the current curriculum design and confronts it with a new "student-centered" learning model that incorporates the students into the learning process in an active and authentic way.